(untitled) (Bangladesh Journal of Botany, 2025)
This research was conducted to evaluate the effectiveness of Novlect (2.13% florpyrauxifen-benzyl and 10.65% cyhalofop), for controlling multiple weed species in rice field. The study included eight treatments: the Novlect premix at three different rates T1, T2 and T3 (1000, 1250, 1500 ml/ha), a sole herbicide T4 (Loyant), three tank mix combinations T5, T6 and T7 (On-duty + Basagran; Nominee + Basagran; Solito + MCPA), and a weedy control plot (T0). Results showed that Novlect at all rates (T1, T2 and T3) effectively controlled weeds such as Leptochloa chinensis (L.) Nees, Echinochloa crus-galli (L.) P.Beauv., Cyperus spp., Monochoria vaginalis (Burm.f.) C.Presl, Ludwigia octovalvis (Jacq.) P.H. Raven, Bacopa rotundifolia (Michx.) Wettst, Sphenoclea zeylanica Gaertn. compared to other applied sole and tank mix herbicide. It caused minimal and recoverable injury to rice at 10-20 days after seeding (DAS). Novlect can be applied between 10-20 DAS, aligning with common practices among farmers for direct-seeded rice. Bangladesh J. Bot. 54(4): 913-918, 2025 (December)